Paraoxonase 2 Induces a Phenotypic Switch in Macrophage Polarization Favoring an M2 Anti-Inflammatory State - Marie Koren-Gluzer; Mira Rosenblat; Tony Hayek (International Journal of Endocrinology)
Inflammatory processes are involved in atherosclerosis development. Macrophages play a major role in the early atherogenesis, and they are present in the atherosclerotic lesion in two phenotypes: proinflammatory (M1) or anti-inflammatory (M2). Paraoxonase 2 (PON2) is expressed in macrophages, and it was shown to protect against atherosclerosis. Thus, the aim of our study was to analyze the direct effect of PON2 on macrophage inflammatory phenotypes. Ex vivo studies were performed with murine peritoneal macrophages (MPM) harvested from control C57BL/6 and PON2-deficient (PON2KO) mice. PON2KO MPM showed an enhanced proinflammatory phenotype compared to the control, both in the basal state and following M1 activation by IFNγ and lipopolysaccharide (LPS). In parallel, PON2KO MPM also showed reduced anti-inflammatory responses in the basal state and also following M2 activation by IL-4. Moreover, the PON2-null MPM demonstrated enhanced phagocytosis and reactive oxygen species (ROS) production in the basal state and following M1 activation. The direct effect of PON2 was shown by transfecting human PON2 (hPON2) into PON2KO MPM. PON2 transfection attenuated the macrophages’ response to M1 activation and enhanced M2 response. These PON2 effects were associated with attenuation of macrophages’ abilities to phagocyte and to generate ROS. We conclude that PON2 promotes an M1 to M2 switch in macrophage phenotypes.